2007
DOI: 10.1128/jb.01076-07
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Promoters Recognized by RNA Polymerase-σ E Holoenzyme from Thermus thermophilus HB8

Abstract: Thermus thermophilusE , an extracytoplasmic function factor from the extremely thermophilic bacterium Thermus thermophilus HB8, bound to the RNA polymerase core enzyme and showed transcriptional activity. With the combination of in vitro transcription assay and GeneChip technology, we identified three promoters recognized by E . The predicted consensus promoter sequence for E is 5-CA(A/T)(A/C)C(A/C)-N 15 -CCGTA-3.Bacterial DNA-dependent RNA polymerase (RNAP) is composed of a core enzyme with the subunit struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…1D), which also revealed the consensus Ϫ10 and Ϫ35 promoter sequences to be at the expected positions. Two types of factors have been reported for T. thermophilus HB8; one is the typical 70 -type factor, designated A , and the other is an extracytoplasmic function factor, designated E (24). The putative sip promoter sequence is in good agreement with the sequence of the T. thermophilus A -dependent promoter (25).…”
Section: Resultssupporting
confidence: 57%
“…1D), which also revealed the consensus Ϫ10 and Ϫ35 promoter sequences to be at the expected positions. Two types of factors have been reported for T. thermophilus HB8; one is the typical 70 -type factor, designated A , and the other is an extracytoplasmic function factor, designated E (24). The putative sip promoter sequence is in good agreement with the sequence of the T. thermophilus A -dependent promoter (25).…”
Section: Resultssupporting
confidence: 57%
“…AP008226, AP008227, and AP008228). T. thermophilus HB8 has a typical bacterial-type RNAP with housekeeping σ factor σ A (Wnendt et al, 1990;Vassylyev et al, 2002) and an ECF σ factor σ E (Shinkai et al, 2007b). We found that the σ E was positively autoregulated, and we identified three σ E -dependent promoters; however, the functions of the σ E -regulated gene products have remain unknown (Shinkai et al, 2007b).…”
Section: Introductionmentioning
confidence: 94%
“…A 0.9-kb NdeI-EcoRI fragment of plasmid pET-His-sigE (Shinkai et al, 2007b) was cloned into the NdeI-EcoRI large fragment of the pET-15b vector (Novagen, Madison, WI) to construct pET-15b-sigE, encoding T. thermophilus σ E with an N-terminal cleavable His tag, M-G-S 2 -H 6 -S 2 -G-L-V-P-R-G-S-H (thrombin recognition site underlined), under the control of a T7 promoter.…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations